Etiopathogenesis of acquired cholesteatoma: prominent theories and recent advances in biomolecular research - Kuo, Chin-Lung (The Laryngoscope, 2015)
To review recent biomolecular advances in etiopathogenesis of acquired cholesteatoma. MEDLINE via OVID (to March 2014) and PubMed (to March 2014). All articles referring to etiopathogenesis of acquired cholesteatoma were identified in the above databases, from which 89 articles were included in this review. The mechanisms underlying the etiopathogenesis of acquired cholesteatoma remain a subject of competing hypotheses. Four theories dominate the debate, including theories of invagination, immigration, squamous metaplasia, and basal cell hyperplasia. However, no single theory has been able to explain the clinical characteristics of all cholesteatoma types: uncoordinated hyperproliferation, invasion, migration, altered differentiation, aggressiveness, and recidivism. Modern technologies have prompted a number of researchers to seek explanations at the molecular level. First, cholesteatomas could be considered an example of uncontrolled cell growth, capable of altering the balance toward cellular hyperproliferation and enhancing the capacity for invasion and osteolysis. Second, the dysregulation of cell growth control involves internal genomic or epigenetic alterations and external stimuli, which induce excessive host immune response to inflammatory and infectious processes. This comprises several complex and dynamic pathophysiologic changes that involve extracellular and intracellular signal transduction cascades. This article summarizes the existing theories and provides conceptual insights into the etiopathogenesis of acquired cholesteatoma, with the aim of stimulating continued efforts to develop a nonsurgical means of treating the disorder.